Flux balance analysis of CHO cells before and after a metabolic switch from lactate production to consumption. Issue 2 (5th November 2012) - Martínez, Verónica S.; Dietmair, Stefanie; Quek, Lake‐Ee; Hodson, Mark P.; Gray, Peter; Nielsen, Lars K.
Abstract: Mammalian cell cultures typically exhibit an energy inefficient phenotype characterized by the consumption of large quantities of glucose and the concomitant production of large quantities of lactate. Under certain conditions, mammalian cells can switch to a more energy efficient state during which lactate is consumed. Using a metabolic model derived from a mouse genome scale model we performed flux balance analysis of Chinese hamster ovary cells before and after a metabolic switch from lactate production (in the presence of glucose) to lactate consumption (after glucose depletion). Despite a residual degree of freedom after accounting for measurements, the calculated flux ranges and associated errors were narrow enough to enable investigation of metabolic changes across the metabolic switch. Surprisingly, the fluxes through the lower part of the TCA cycle from oxoglutarate to malate were very similar (around 60 µmol/gDW/h) for both phases. A detailed analysis of the energy metabolism showed that cells consuming lactate have an energy efficiency (total ATP produced per total C‐mol substrate consumed) six times greater than lactate producing cells. Biotechnol. Bioeng. 2013; 110: 660–666. © 2012 Wiley Periodicals, Inc. Abstract : The authors studied the metabolism of CHO cells before and after a metabolic switch from lactate production to consumption when glucose is depleted. The activity of TCA cycle remained the same despite the switch in carbon source, but the fraction of acetyl‐CoA catabolized to CO2 increased from 3% to 32%. The metabolic model in this study was derived from a mouse genome scale model. Despite the model being underdetermined, the estimated flux ranges were sufficiently constrained to allow meaningful comparative analyses.